Origin of tropical American burrowing reptiles by transatlantic rafting - Vidal, Nicolas (The Royal Society, 2007)
Populations of terrestrial or freshwater taxa that are separated by oceans can be explained by either oceanic dispersal or fragmentation of a previously contiguous land mass. Amphisbaenians, the worm lizards (approx. 165 species), are small squamate reptiles that are uniquely adapted to a burrowing lifestyle and inhabit Africa, South America, Caribbean Islands, North America, Europe and the Middle East. All but a few species are limbless and they rarely leave their subterranean burrows. Given their peculiar habits, the distribution of amphisbaenians has been assumed to be primarily the result of two land-mass fragmentation events: the split of the supercontinent Pangaea starting 200 Myr ago, separating species on the northern land mass (Laurasia) from those on the southern land mass (Gondwana), and the split of South America from Africa 100 Myr ago. Here we show with molecular evidence that oceanic dispersal—on floating islands—played a more prominent role, and that amphisbaenians crossed the Atlantic Ocean in the Eocene (40 Myr ago) resulting in a tropical American radiation representing one-half of all known amphisbaenian species. Until now, only four or five transatlantic dispersal events were known in terrestrial vertebrates. Significantly, this is the first such dispersal event to involve a group that burrows, an unexpected lifestyle for an oceanic disperser.